2012
DOI: 10.1039/c2cc16727a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of a novel ionic liquid derived mesoporous carbon

Abstract: A novel nano-fibrillated mesoporous carbon (IFMC) was found to be an effective modifier in combination with ionic liquid 1-octylpyridinum hexafluorophosphate (OPFP) as a binder to give impregnated graphite electrodes with outstanding electrochemical performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…S1), a characteristic reported previously [23], were clearly observed in the HRTEM images of the prepared Pd@ IFMC.…”
Section: Characterization Of Pd@ifmcsupporting
confidence: 53%
See 3 more Smart Citations
“…S1), a characteristic reported previously [23], were clearly observed in the HRTEM images of the prepared Pd@ IFMC.…”
Section: Characterization Of Pd@ifmcsupporting
confidence: 53%
“…1-Methyl-3-phenethyl-1H-imidazolium hydrogen sulfate (MPIHS) was used as carbon source. Ionic liquid derived fibrillated mesoporous carbon (IFMC) was prepared based on the method reported previously [23] by the use of SBA-15 and MPIHS. Pd nanoparticles decorated ionic liquid derived fibrillated mesoporous carbon (Pd@IFMC) was prepared based on the method reported previously [24,26].…”
Section: Synthesis Of Pd@ifmcmentioning
confidence: 99%
See 2 more Smart Citations
“…32 It is concluded that dispersing the MnO 2 nanoparticles on conductive substrates could result in accomplishing the redox reactions in the charge storage mechanism by enhancing the electrical conductivity of the MnO 2 based electrodes. 1,45,47,48 Herein, we investigate the incorporation of MnO 2 nanoparticles within IFMC and the resulting supercapacitive behavior. 34 Two important shortcomings of commercial supercapacitor materials are the limited specic capacitance of the carbon materials, in addition to the low energy density.…”
Section: Introductionmentioning
confidence: 99%